Expression of largest RNA segment and synthesis of VP1 protein of bluetongue virus in insect cells by recombinant baculovirus: association of VP1 protein with RNA polymerase activity. - Urakawa, T (1989)
The bluetongue virus core particles have been shown to contain an RNA-directed RNA polymerase (1). To identify the protein responsible for the virion RNA polymerase activity, the complete 3.9 Kb DNA clone representing the largest RNA segment 1 (L1) of bluetongue virus (BTV-10) was placed under control of the polyhedrin promoter of Autographa californica nuclear polyhedrosis virus (AcNPV). The derived recombinant virus was used to infect Spodoptera frugiperda cells. As demonstrated by stained polyacrylamide gel electrophoresis and by the use of bluetongue virus antibody, infected insect cells synthesized the largest protein of BTV-10 (VP1, 150 k Da). Antibody raised in rabbit to recombinant VP1 protein recognized bluetongue virus VP1 protein. The recombinant virus infected cell lysate had significantly inducible levels of RNA polymerase enzymatic activity as determined by a poly (U)-oligo (A) polymerase assay. The availability of enzymatically active bluetongue virus RNA polymerase provides a system in which we can precisely delineate the role this protein plays in the regulation of bluetongue replication.